PENGARUH MODEL PROJECT BASED LEARNING DAN KOMPETENSI PROFESIONAL GURU TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA - Untu, Hadi Ignatius; Tuegeh, Christofel; Kapoh, Veronica; Selviana, Selviana (Bahasa Indonesia, 2025)
This study aims to analyze the influence of the Problem-Based Learning (PBL) model and teacher professional competence on students' critical thinking skills at SMP Lokon St. Nikolaus Tomohon, both partially and simultaneously. The approach used is quantitative, with a population of 239 students and a sample of 149 respondents determined using the Slovin formula. The research instrument consists of a questionnaire with a Likert scale, and the analysis technique used is multiple linear regression. The results of the study indicate that the PBL model partially influences students' critical thinking skills by 29.1% (moderate category), while teachers' professional competencies influence them by 11.6% (low category). Simultaneously, both variables contribute 42.1% to students' critical thinking skills, which is classified as good.